Grieving, brooding, transforming: the spirit, the Bible, and gender - Johns, Cheryl B.; Stephenson, Lisa P. (Journal of pentecostal theology / Supplement series, 2021)
"Grieving, Brooding, and Transforming: The Spirit, The Bible, and Gender is a collection of scholarly essays by Pentecostal women. It explores troubling biblical texts, as well as those of contemporary church life, in regards to the portrayal of women. The authors seek to identify the presence and work of the Spirit that is often hidden within the contours of these texts. A Pentecostal feminist hermeneutic desires to move beyond suspicion into the deeper terrain of the Spirit's mission of grieving, brooding, and transforming a broken world. The essays point to the purposes of God toward justice and the healing of creation"--